Efficacy of vitamin E and selenium for the prevention of intra-abdominal adhesions in rats: uterine horn models - Durmus, Ali Said; Yildiz, Hamit; Yaman, Ihsan; Simsek, Halil (Elsevier Espana, 2011)
OBJECTIVE: This study compares the efficacies of vitamin E and selenium, both individually and in combination, for the prevention of postoperative intra-abdominal adhesions in rats. METHODS: Forty-seven female rats were divided into five groups. The sham animals (S group, n = 7) were given only laparotomies and intraperitoneally received 0.9% NaCl (2 ml). In the 40 other rats, abrasions of the left uterine horn were performed, followed by intraperitoneal administration of either 2 ml 0.9% NaCl (C group), 10 mg vitamin E (vitamin E group), 0.2 mg/kg selenium (Se group) or 10 mg vitamin E with 0.2 mg/kg selenium (vitamin E + Se group), with 10 animals in each treatment group. RESULTS: Adhesion formation was significantly reduced in animals in the Se and vitamin E + Se groups (p<0.05). Tissue catalase and glutathione peroxidase activities did not significantly differ between the groups. However, catalase and glutathione peroxidase activities and reduced glutathione levels were slightly increased in the vitamin E, Se and vitamin E + Se groups. In the vitamin E group, malondialdehyde concentrations were significantly lower than in the C group (p<0.05), but no significant differences were present among the S, C, Se and vitamin E + Se groups. Levels of nitric oxide were significantly higher in the C group than in the other groups (p<0.01). CONCLUSION: Intraperitoneal administration of selenium or combined vitamin E and selenium appears to be effective in preventing intra-abdominal adhesion formation in rat models through the reduction of lipid peroxidation products.
Keywords: Vitamin E; Selenium; Intra-abdominal adhesion; Histopathology; Rat